EVALUASI PENGGUNAAN KOMBINASI ZINK DAN PROBIOTIK PADA PENANGANAN PASIEN DIARE ANAK DI INSTALASI RAWAT INAP RSUD UNDATA PALU TAHUN 2013 - Lolopayung, Mardiyani; Mukaddas, Alwiyah; Faustine, Inggrid (Natural Science: Journal of Science and Technology, 2014)
Diarrhea is one of the main causes of child morbility and mortality in developing countries. Giving zinc and probiotics to children who get diarrhea, it can give positive impact on the incidence of diarrhea. This research aimed to evaluate the use of zinc and probiotics in treatment of children diarrhea. This research was conducted by using prospective method to children diarrhea in children?s ward Catelia at RSUD Undata Palu from June to September 2013. The subject on this research were divided into 2 groups, test and control group. The test group received therapy Oral Rehydration Salts (ORS),  in combination to zinc ? probiotic treatment, and the control group only received ORS. Observed variable are the change of stool consistency,  frequency, diarrhea duration, and lenght of stay. The result of changing stool consistency in test group was better than it in control group. The mean frequency of diarrhea while out in the test group was 1,27 ± 0,45 and it in control group was 1,53 ± 0,56. Lenght of stay in treated group (3,27 ± 1,26) was shorter  than it in control group (3,77 ± 1,00). The use of zinc and probiotics for children diarrhea patients have significant effect on stool consistency, diarrhea frequency, diarrhea duration and lenght of stay (p=0,000).